2011
DOI: 10.5402/2011/527453
|View full text |Cite
|
Sign up to set email alerts
|

Brain Metastases from Ovarian Carcinoma

Abstract: This paper will focus on knowledge related to brain metastases from ovarian carcinoma. So far, less than 600 cases were documented in the literature with an incidence among ovarian carcinoma patients ranging from 0.29% to 11.6%. The ovarian carcinoma was usually an advanced-stage epithelial serous carcinoma, and the median interval between diagnosis of ovarian carcinoma and brain metastases was 2 years. Most often, brain metastases, affected the cerebrum, were multiple and part of a disseminated disease. Treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
76
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(82 citation statements)
references
References 73 publications
4
76
0
1
Order By: Relevance
“…[9] In 2011, Piura E and piura B reported 521 cases between 1978 and 2011. [10], while in 2014, Pakneshan et al reported 591 cases between 1978 and 2013. [11] Piura and Piura determined the incidence of brain metastases from ovarian cancer to be 1.2% [10], which was twice the incidence associated with cervical [12] or endometrial cancer [13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[9] In 2011, Piura E and piura B reported 521 cases between 1978 and 2011. [10], while in 2014, Pakneshan et al reported 591 cases between 1978 and 2013. [11] Piura and Piura determined the incidence of brain metastases from ovarian cancer to be 1.2% [10], which was twice the incidence associated with cervical [12] or endometrial cancer [13].…”
Section: Discussionmentioning
confidence: 99%
“…[10], while in 2014, Pakneshan et al reported 591 cases between 1978 and 2013. [11] Piura and Piura determined the incidence of brain metastases from ovarian cancer to be 1.2% [10], which was twice the incidence associated with cervical [12] or endometrial cancer [13]. Pakneshan et al reported that the incidence among the various studies ranged from 0.49 to 11.4%, with an average of 2.55% [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Медиана возраста пациенток в той работе была 58 лет, медиана выживаемости только при МГМ 3,9 месяцев, при наличии вместе с МГМ еще и экстракраниального пораже-ния -3,9 месяцев [14]. В целом, МГМ рака яичников отграничены небольшими сериями и отдельными описаниями случаев, коих в ли-тературе на конец 2011 года насчитывалось не более 600 [15]. Рак шейки матки обычно имеет местное распространение и чаще дает метастазы по лимфатическим путям в забрюшинные лимфа-тические узлы [9,13].…”
Section: Discussionunclassified